The decline in robbery and theft: inter-state comparisons - Don Weatherburn
This paper finds that the national decline in robbery and theft offences is partly due to a reduction in heroin use and partly due to improvements in the economy, but that other factors are likely to have also played a role.Aim: To describe and discuss inter-jurisdictional trends in police-recorded robbery and theft offences.Method: Rates of recorded robbery and theft per head of population are calculated for each Australian jurisdiction from 1994/1995 to 2012. Rates of recorded robbery are disaggregated into armed and unarmed robbery. Rates of recorded theft are disaggregated into burglary, motor vehicle theft and other theft.Results: In most jurisdictions, trends in recorded robbery and theft offences rose during the late 1990s, peaked around 2001 and then fell from 2001 to 2012. Between 2001 and 2009, recorded rates of robbery offences in Australia fell by 49.1 per cent, recorded rates of burglary fell by 57.3 per cent, recorded rates of motor vehicle theft fell by 62.2 per cent and recorded rates of other theft fell by 39.3 per cent.Conclusion: The national decline in robbery and theft offences is partly due to a reduction in heroin use and partly due to improvements in the economy but other factors are likely to have also played a role. Research into the causes of the fall in crime is hampered by the absence of any regional breakdown in national recorded crime statistics